دور المقاولاتية في تحقيق كفاءة أداء المنظمة - نعام, يوسف (جامعة الوادي University of Eloued, 2019)
من خلال عرض مختلف المساهمات التى ترجمت تطور الفكر المقاولاتي واعتبار أن المقاولاتية ظاهرة اجتماعية ترتكز في الأساس على شخص المقاول ، و إنها تعبير لتحويل لإمكانات والطاقات البشرية إلى كيانات اقتصادية رائدة في مجال الأعمال وبالتالي تحقيق التوازن الاقتصادي والاجتماعي ، لتحقيق المقاولة لكفاءة أداءها ، هناك مؤشرات ومعايير كمية كيفية ، فالكمية تعاني القصور في قياس الكفاءة المقاولة ، لذا فان المقاييس غير مباشرة الكيفية تعد الطريق الأفضل لقياس كفاءة المقاولة . وباعتبار ان الإبداع والابتكار والمخاطرة وسرعة الانجاز سمات المقاولة. .فقد اعتمدت كمؤشرات لقياس كفاءة المقاولة . Through the presentation of various contributions that translated the development of corporate thought and consider that the entrepreneurial social phenomenon based primarily on the person of the contractor, and it is an expression to transform the potential and human potential to economic entities leading in business and thus achieve economic and social balance, to achieve the efficiency of its performance, Quantities of how, the quantity is deficient in measuring the efficiency of the contract, so the indirect measures how the best way to measure the efficiency of the enterprise. Creativity, innovation, risk and fast delivery are the characteristics of entrepreneurship. It has been adopted as indicators to measure the efficiency of the enterprise.
ماستر سياسة عامة
Keywords: المقاول ، المقاولة ، الكفاءة ، الابداع و الابتكار، ادارة الخطر ،ادارة الوقت; "contractor, contractor, efficiency, innovation and innovation, risk management, time management "